The analgesic efficacy of ultrasound-guided modified rectus sheath block compared with wound infiltration in reduction of postoperative morphine consumption in women undergoing open hysterectomy or myomectomy: A randomized controlled trial 14/09/2012 trial - Mukesh Kumar Shah; Sandeep S Kulkarni; Wendy Fun (Wolters Kluwer Medknow Publications, 2012)
Introduction: As ultrasound allows more accurate placement of local anesthetic (LA), ultrasound-guided modified rectus sheath block (MRSB) was compared with wound infiltration (WI) in women having open hysterectomy or myomectomy for fibroids via a Pfannenstiel incision under general anesthesia. Materials and Methods: Forty-two American Society of Anesthesiologists Class ASA I,II and III patients were recruited into two groups in a randomized patient-blinded controlled trial excluding those with coagulopathy, infection, or LA allergy. At the end of surgery, in the study group (Group U), an MRSB, under ultrasound guidance, was administered with 20 ml 0.25% levobupivacaine through a single skin puncture in the midline, 2 cm below the umbilicus, on either side of the midline, above the posterior sheath. In the control group (Group W), WI with 20 ml 0.5% levobupivacaine was done by the surgeon. The primary outcome measure was the amount of morphine consumed in the first 24 h after the surgery in the ward. Statistical analysis was performed with SPSS v.14.0. Results: Morphine consumption in the intraoperative and recovery periods was 10 mg and 0.0 mg, respectively, in both groups. In both the groups, pain measured by visual analog scale correct (VAS) (both at rest and on movement), morphine consumption (12.0 mg [18.0 mg] vs. 12.0 mg [23.0 mg], median interquartile range [IQR], p = 0.950), and the number of oral analgesic doses administered during the study period were comparable. However, number of patients who were "extremely satisfied" compared to "satisfied" with the analgesia were more in the Group U than in Group W (15/6 vs. 4/17, P-0.001). Sedation, nausea and vomiting, and antiemetic doses given were minimal and comparable in both groups. Conclusion: Ultrasound-guided MRSB does not show any significant difference in the 24 h morphine consumption as compared to WI.